DEVELOPMENT OF EMOTIONAL INTELLECT IS IN THE PROCESS OF PROFESSIONAL PREPARATION OF PSYCHOLOGIST - Dubrovynskyi, Geogyi (PSYCHOLOGICAL JOURNAL, 2020)
The process of forming of readiness of students-psychologists to future professional activity has universal character and sent not only to the capture a professional psychological tool but also on the personality changes of future psychologists in the process of realization of educational-professional activity. Preparation of psychologist in establishments of higher education (EHE) must answer the requirements of time, and the choice of speciality determines priorities in studies, in determination of itself, forming own I in a paradigm - get to know itself. We used a methodological toolkit in the form of an in-depth interview with students of the first year of Taras Shevchenko KNU to determine the impact of computer robotics on the choice of future specialty. There is also a correlation between the level of EI and the level of creativity during the study of students of the 8th grade of Physics and Mathematics Lyceum of the Shevchenko National University of Kyiv, according to the results of the EI test by Nicholas Hall, diagnostics of E.E.Tunik’s personal creativity, J. Raven’s level of mental intelligence, success in teaching and questioning, which identified the main hobbies of students.In our work we considered the question of readiness to the studies of the students based on principles of methodical level during professional preparation in ЗВО, as means of increase of emotional intellect (ЕІ). Gave mind on such pre-conditions of development of ЕІ, as: biological, social, age-old, professionally-developing. Explaining biological constituents we were stopped for the features of structure and development of organism of man, heredity of making of emotional capabilities, temperament, and also the biological principles of научуваності personality, expounded in the monograph of Zaritskaya V.V.; social constituents are on descriptions of given Andreeva I. social constituents on descriptions of given Андрєєвою І. Age-old positions occupied a certain division into periods, including expounded Дерев’янко С.П., gave mind on: to the emotional orientation, self-contradictions in a period becoming of consciousness, mobility and plasticity of мовленєвого stereotype, flexibility of thinking, sequence of changes of thinking. What touches readiness of student to professionally-developing activity, then we exposed such concepts, as: emotionality, emotional firmness and emotional potential of personality. In further by us the signs of high level of ЕІ and influence of emotional intellect are distinguished on development of professional reflection of personality.